Cytogenotoxic evaluation of the acetonitrile extract, citrinin and dicitrinin-A from Penicillium citrinum - de Oliveira Filho, José Williams Gomes (2020)
Endophytic fungi are promising sources of bioactive substances; however, their secondary metabolites are toxic to plants, animals, and humans. This study aimed toevaluate the toxic, cytotoxic, mutagenic and oxidant/antioxidant activities of acetonitrile extract (AEPc), citrinin (CIT) and dicitrinin-A (DIC-A) of Penicillium citrinum. For this, the test substances at 0.5; 1.0; 1.5 and 2 μg/mLwere exposed for 24 and 48 h in Artemia salina, and 48 h in Allium cepa test systems. The oxidant/antioxidant test was evaluated in pre-, co- and post-treatment with the stressor hydrogen peroxide (H2O2) in Saccharomyces cerevisiae. The results suggest that the AEPc, CIT and DIC-A at 0.5; 1.0; 1.5 and 2 μg/mL showed toxicity in A. saline, with LC50 (24 h) of 2.03 μg/mL, 1.71 μg/mL and 2.29 μg/mL, and LC50 (48 h) of 0.51 μg/mL, 0.54 μg/mL and 0.54 μg/mL, respectively.In A. cepa, the test substances also exerted cytotoxic and mutagenic effects. The AEPc, CIT and DIC-A at lower concentrations modulated the damage induced by H2O2 in the proficient and mutant strains of S. cerevisiae for cytoplasmic and mitochondrial superoxide dismutase. Moreover, the AEPc at 2 μg/mL and CIT at the two highest concentrations did not affect the H2O2-induced DNA damage in the test strains. In conclusion, AEPc, CIT and DIC-A of P. citrinum may exert their toxic, cytotoxic and mutagenic effects in the test systems possibly through oxidative stress induction pathway.